Profesional attachment at Ohio University United States of America / Mawar Noor Abullah - Abdullah, Mawar Noor (UiTM Cawangan Johor, 2010)
This report is prepared for Human Resource Department UiTM Malaysia as a requirement for a librarian professional attachment at Ohio University Libraries & Center for International Collections, United States of America on May 1 until October 31, 2010. This professional attachment is a collaboration program between UiTM and Ohio University. It’s also contribute to the renewed partnership between Ohio and Universiti Teknologi MARA (UiTM), which Center for International Studies was pleased to help initiate during a visit to Malaysia in July 2009. The cost of this visit including rent, medical insurance, expense stipend are covered by Ohio University Libraries, Ohio University Center for International Studies as well as salary paid by University Teknologi MARA.